KEWENANGAN DEWAN PERWAKILAN DAERAH DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DIKAITKAN DENGAN SISTEM BICAMERAL - Muhammad Nadzir; Suhartini (Fakultas Hukum Universitas Hang Tuah, 2021)
This study aims to answer the formulation of the first problem, what is the authority of the Regional Representatives Council (DPD) in the formation of laws and regulations? Second, does the authority of the Regional Representatives Council in the formation of these laws and regulations reflect the representative institutions of the bicameral system? The conclusion is that the DPD has the authority in the field of Legislation at the following stages: This study uses a normative juridical approach, namely research that analyzes a legal problem by conducting a literature study, both from primary, secondary and tertiary legal materials. The analysis of research data is qualitative in nature, namely concluding and describing the answers to the legal problems under study. byplanning, preparation and discussion related to bills related to regional autonomy, the formation and expansion and merging of regions, natural resource management, as well as those relating to the balance of central and regional finance. The DPD has the authority to provide considerations in the Tax Bill, APBN, Education and religion to the DPR. Second, the two-chamber representation system (Bicameral) provides an equally strong position, this applies to the DPD and the DPR. In implementing the Representative system, the DPD has weak authority in various functions, both legislation, supervision and budgeting. The weakness of the legislative function can be seen from the DPD's inability to participate in discussing the decision making the bill into law. This shows that the DPD's authority does not reflect as a pure bicameral system representative institution, but reflects a soft bicameral representation system.